The mediating role of work motivation in the relationship between work ethics, workload, and work commitment among service company employees in Klang Valley, Malaysia - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Rosnon, Mohd Roslan (Human Resources Management Academic Research Society, 2024)
This study explores the mediating role of work motivation in the relationships between work ethics, workload, and work commitment among employees in service companies in Klang Valley, Malaysia. Utilizing a cross-sectional survey of 382 employees from various courier service companies, the research employs established instruments to measure the constructs. The results indicate that work ethics and workload are significant predictors of work commitment, with work motivation serving as a crucial mediator. Employees with strong work ethics and manageable workloads are more likely to be motivated and committed to their organizations. This highlights the importance of fostering ethical work environments, balancing workloads, and enhancing employee motivation to improve organizational commitment. Practical strategies suggested include implementing ethical training programs, managing workloads effectively, and providing intrinsic and extrinsic motivational incentives. In conclusion, the study provides empirical evidence on the mediating role of work motivation in the relationships between work ethics, workload, and work commitment. By understanding these dynamics, organizations can develop targeted strategies to foster a committed and motivated workforce, ultimately improving organizational performance and sustainability. These findings offer valuable insights for both academics and practitioners in employee engagement and organizational development.